Analisis Pemenuhan Persyaratan Subbab 103 dan 106 US FDA FSMA di Industri Minyak Cengkeh Indonesia - Lendrawati, Lendrawati; Hariyadi, Ratih Dewanti; Wulandari, Nur (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2016)
Nowadays, intentional contamination of food product has become an additional concern in food safety management system (FSMS) such as that in the United State Food Drug Adminstration (US FDA) Food Safety Modernization Act (FSMA). Therefore, it is necessary to raise awareness and take into consideration of intentional contamination into any production chain. The purpose of this study was to provide recommendation for updating the FSMS in PT XYZ to integrate intentional contamination. The research was conducted by reviewing regulations related to the safety of clove oil as flavoring agents, identify adulterant compounds in clove oil, assessing the existing food safety management system in PT XYZ, performing gap analysis using the main provision of FSMA pertaining hazard analysis and risk-based preventive controls (section 103) and protection against intentional adulteration (section 106) as reference, and developing recommendations for the gaps. Pertaining to section 103 and section 106 requirements, the assessment suggested that PT XYZ fullfilled 54% of the requirements i.e 52% (section 103) and 2% (section 106). Education to raise employee awareness and develop a food defense plan are recommended to meet the FSMA requirement.